Pemanfaatan Teknologi Digital dalam Upaya Memperkuat Ekonomi Digital pada Koperasi Simpan Pinjam di Desa Sobangan Mengwi - Trisnadewi, Anak Agung Ayu Erna; Purnami, Anak Agung Sri (JURNAL SEWAKA BHAKTI, 2024)
Cooperatives as a form of microfinance institutions are known as pillars or cornerstones of the economy. However, not much has been heard of the actions of cooperatives that are capable of becoming cooperatives on a national, international scale or using digital financial services. The existence of digitalization of cooperatives has a goal orientation for convenience, speed of service, comfort, and security when making transactions with cooperatives. In addition, efforts to digitize cooperatives are expected to accelerate the growth of cooperatives. With digitalization, cooperatives are able to expand their business scale to remote areas. Based on the situation analysis of Candra Sedana's KSP partners, various problems and limitations have been found which can be identified as follows: partners' lack of knowledge about the concept of digital transformation regarding cooperative financial information systems that are connected to the banking system and QRIS adoption and partners' lack of knowledge about the concept of change management. The solutions offered related to partner problem solving are as follows: Providing counseling regarding the concept of 'change management', Providing counseling regarding the concept of digital transformation regarding literacy regarding cooperative financial information systems that are connected to banking and the QRIS concept of optimal utilization, as well as implementing assistance and direct practice regarding the adoption of information systems and QRIS development.